2012
DOI: 10.1364/oe.20.019194
|View full text |Cite
|
Sign up to set email alerts
|

Highly reliable Ag/Zn/Ag ohmic reflector for high-power GaN-based vertical light-emitting diode

Abstract: We report the improved performance of InGaN/GaN-based light-emitting diodes (LEDs) through Ag reflectors combined with a Zn middle layer. It is shown that the Zn middle layer (5 nm thick) suppresses the agglomeration of Ag reflectors by forming ZnO and dissolving into Ag. The Ag/Zn/Ag contacts show a specific contact resistance of 6.2 × 10(-5) Ωcm(2) and reflectance of ~83% at a wavelength of 440 nm when annealed at 500 °C, which are much better than those of Ag only contacts. Blue LEDs fabricated with the 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The XPS results (not shown) showed that both the samples revealed a shift of the surface Fermi level toward the valence-band edge when annealed at 500°C, resulting in a reduction in the effective Schottky barrier height and thereby lowering the contact resistivity. The surface Fermi level shift is related to the generation of acceptorlike Ga vacancies caused by the formation of an Ag-Ga solid solution, as confirmed by the XPS depth profile results (not shown) and the resulting increase in the carrier concentration at the surface region [4,5,15]. The reason that the Mg-inserted Ag sample showed better electrical performance than the Ag-only sample can be attributed to a larger contact area between GaN and Ag layers due to the delayed agglomeration (Fig.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…The XPS results (not shown) showed that both the samples revealed a shift of the surface Fermi level toward the valence-band edge when annealed at 500°C, resulting in a reduction in the effective Schottky barrier height and thereby lowering the contact resistivity. The surface Fermi level shift is related to the generation of acceptorlike Ga vacancies caused by the formation of an Ag-Ga solid solution, as confirmed by the XPS depth profile results (not shown) and the resulting increase in the carrier concentration at the surface region [4,5,15]. The reason that the Mg-inserted Ag sample showed better electrical performance than the Ag-only sample can be attributed to a larger contact area between GaN and Ag layers due to the delayed agglomeration (Fig.…”
mentioning
confidence: 59%
“…However, it suffers from agglomeration when annealed at temperatures above 300°C. To enhance the thermal reliability of Ag-based contacts, a variety of methods, such as overlayers [6][7][8], Ag alloys [9][10][11], interlayers [12][13][14] and inserted layers [15], have been used. For example, the use of overlayers, such as films of La [6], Zn [7] or Ru [8], was shown to considerably improve the thermal stability of Ag reflectors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work [22], we showed that an Ag/Ni/Ag multilayer scheme produces reflectors with good thermal stability. LEDs fabricated with these multilayer reflectors gave more light than LEDs with Ag-only reflectors.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, vertical-structure GaN-based LEDs fabricated with ITO/Ni/Ag contacts capped with Ni/Au and W/Cu layers showed a higher output power (at 350 mA) than those fabricated with ITO/Ni/Ag contacts. Yum and co-workers [13] reported that the use of a zinc middle layer was effective in increasing the thermal stability of Ag reflector and resultant LEDs with the Ag/Zn/Ag reflector showed higher light output than LEDs with Ag only reflector. It was also found that the use of capping layers, such as Pt [12], Zn [14], La [15], and Ru films [16], effectively improves the thermal stability.…”
Section: Introductionmentioning
confidence: 99%